Kontribusi Mahasiswa KKN Universitas Sunan Giri Surabaya Terhadap UMKM Ayam Panggang Rakyat Mbah Romlah Dusun Bulang Desa Kloposepuluh - Shakilla Fajri Angelina; Mujia Yahdillah; Rahayu Mardikaningsih; Siti Nur Halizah; Didit Darmawan; Muchammad Catur Rizky; Rommy Hardyansah (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
As a step to expand outreach and increase community awareness, the research plan proposes providing new banners and ensuring that MSME locations are listed on Google Maps. The priority justification prioritizes optimizing potential through community empowerment with the support of the Community Service program. The focus on increasing awareness of packaging through an importance survey, developing appropriate technology, and expanding marketing networks aims to strengthen the competitiveness of MSMEs' processed food products. The ABCD approach was chosen to emphasize the utilization of existing assets in the community, so as to maximize the potential of the People's Roasted Chicken MSMEs and empower the community in a sustainable manner. The results of this study indicate that the People's Roast Chicken MSME in Kloposepuluh Village has its own uniqueness with a characteristic taste that has been maintained from the past until now, making it a favorite among the local community. The strategic sales location, right in front of the house, adds to the attractiveness for customers. Although they still use traditional methods in baking, these MSMEs have managed to survive and continue to be in demand.